Delimitação de áreas variáveis de afluência em ambientes de microbacias urbanas através da comparação dos métodos TauDEM e HAND - Bressiani, Jaciane Xavier (2016)
According to the Brazilian Forest Code, law nº 12.651/12, the permanent preservation areas (PPA) are a symmetric range of vegetation that have their width specified proportionally to the water flow width. Therefore, to attend legislation demands, the PPA delimitation follows very simple rules which does not consider physical and dynamics aspects of the riparian ecosystem and does not require the knowledge in techniques for hydrologic modeling. In this context, the areas variable inflow (AVI) are an alternative for the delimitation of the riparian areas ensuring the environmental functions performed by them. The AVIs are little areas in the watershed that are expanded and contracted because of the precipitation events that saturate the soil and they are not always coincident with the PPAs. The AVIs are areas associated to the quality of the hydric resources, once they are a superficial source flow arising from saturation and so, the AVIs can transport sediments and pollutants to the water flows. Thus, the main goal of the reserach is to compare models that define the boudaries of AVIs located at urban watershed by means of topographic and hydrologic parameters. The models were obtained through \'Terrain Analysis Using Digital Elevation Models (TauDEM) and Height Above the Nearest Drainage (HAND), having as the study areas the watersheds from Lagoinha and the Campo Alegre, in the city of Uberlândia, in Minas Gerais. Despite both models use the digital terrain model (DTM) from topographic data, TauDEM performs a correlation between it and its specific contribution area, and on HAND, there is a correlation with the nearest drainage network. It is found that the AVIs include PPAs as part of them, however, the first ones are distributed for the entire watershed, and quantitatively, they are spread over bigger areas than those defined by the Brazilian Forest Code. It was possible to make a map of susceptibility of the watershed using these specialized areas and buffers from the APPs and maps of land use. The map aims to help the management of the watershed for maintenance and preservation of the AVAs that are not contemplated by the present legislations as APP